Security Threats and Solutions in Operating Systems (International Journal of Food and Nutritional Sciences, 2022)
A distributed operating system is software that runs over several separate, connected, communicative, and computational nodes that are physically distinct. Each node in the network has a certain subset of the software. The global operating system for all computers each grouping is a combination of two different service providers. The initial is a minimal kernel, sometimes known as a microkernel that controls the hardware of that node. Second, a more advanced level set of management components for systems that synchronize the node's individual and group efforts activities. These elements represent the microkernel functionalities and user applications support. The management components and the microkernel collection cooperate. There are now several affordable and easily accessible network gadgets for the home, including remote-controllable locks, lights, thermostats, cameras, and motion sensors. Theoretically, this permits situations like remote video monitoring from a smartphone or customized occupant patterns-based climate control. However, such smart home scenarios are scarcely used in practice today. This study explores the security threats and solutions in operating systems.